2020
DOI: 10.1111/auar.12315
|View full text |Cite
|
Sign up to set email alerts
|

Executive Compensation and Financial Performance Measures: Evidence from Significant Financial Institutions

Abstract: We survey the use of financial performance measures in determining executive pay among significant Australian financial institutions. We document evidence of the pervasiveness with which externally disclosed non‐GAAP (non‐Generally Accepted Accounting Principles) financial measures are also used internally to determine variable remuneration, with the apparent popularity of cash profit after tax in short‐term incentives plans. Our evidence also highlights the increasing use of peer group‐adjusted measures (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Our findings are generally consistent with previous studies in the countries, for which the Anglo-American is more suitable, e.g. in the US, Japan, Australia, and New Zealand, such as those of: (1) Lin and Shi (2020), who show that there is a positive relationship between firm market performance and CEO pay; Kato and Kubo (2006), who find that Japanese CEO's cash compensation is sensitive to firm performance; Le et al (2020), who document evidence of the pervasiveness of financial measures used in the assessment of variable remuneration among financial institutions; Ding and Chea (2021), who report that the employee stock option is positively related to firm performance. In emerging economies, the relationships between CEO pay and firm performance are heterogeneous.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are generally consistent with previous studies in the countries, for which the Anglo-American is more suitable, e.g. in the US, Japan, Australia, and New Zealand, such as those of: (1) Lin and Shi (2020), who show that there is a positive relationship between firm market performance and CEO pay; Kato and Kubo (2006), who find that Japanese CEO's cash compensation is sensitive to firm performance; Le et al (2020), who document evidence of the pervasiveness of financial measures used in the assessment of variable remuneration among financial institutions; Ding and Chea (2021), who report that the employee stock option is positively related to firm performance. In emerging economies, the relationships between CEO pay and firm performance are heterogeneous.…”
Section: Discussionsupporting
confidence: 92%
“…The level of compensation offered to chief executive officers (CEOs) and the relationship between executive pay and companies' financial performance are among the issues that the corporate governance literature deals with the most often. This topic was discussed in the last several decades (Jensen & Murphy, 1990;Mäkinen, 2005;Kato & Kubo, 2006;Brick et al, 2006;Iwu-Egwuonwu, 2010;Ozkan, 2011;Raithatha & Komera, 2016;Amarou & Bensaid, 2017;Yamina & Mohamed, 2017) as well as in recent years (Le et al, 2020;Lin & Shi, 2020;Dias et al, 2020;Amewu & Alagidede, 2021;Cui et al, 2021;Ding & Chea, 2021;Wang et al, 2021;Chen & Hassan, 2022;Kayani & Gan, 2022). Nonetheless, some authors have demonstrated empirically that the relationship between executive compensation and financial performance is significant and positive, while others have not found such a relationship at all.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kabir and Thai (2017) document the moderating effect of different aspects of corporate governance on the relationship between CSR and financial performance. Le et al (2020) document that externally disclosed non-Generally Accepted Accounting Principles (non-GAAP) financial measures are also used internally to determine remuneration. Matolcsy and Wright (2011) find that firms whose CEOs receive compensation inconsistent with their firm characteristics have lower performance than firms whose CEOs’ compensation is consistent with their firms’ performance.…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%
“…Financial performance can be measured using various operational indicators. According to Le, Shan, and Taylor (2020), the main financial performance measures are; the return on equity (ROE), return on assets (ROA), leverage, liquidity, firm size, and Tobin's Q among others.…”
Section: Introductionmentioning
confidence: 99%